Memperlajari teknik menghafal: Metode yang pernah di terapkan oleh para peserta Clash of Champions dalam sebuah kompetisi bergengsi - Farida, Nurul (Maliki Interdisciplinary Journal, 2026)
The human brain as a complex control center, its tasks are not limited to storing memory alone; they include controlling emotions, reflexes, and even the functions of other organs in the body. There are many aspects of the human brain that I have always wanted to explore—the complexity of each component, its functions, and how it operates to maintain stability in our lives. This is not an exhaustive discussion; this journal only addresses one of many topics, namely the methods or techniques to prompt the brain to retrieve information we wish to recall, such as during exams. During exams, we certainly need the ability to access the information we have learned. Logically, this technique utilizes association, visualization, spatial allocation, and emotional involvement. Thus, with this technique, we do not spend excessive time retrieving the information. Previously, I also investigated what causes the brain to recall information that has been stored for a long time. Sometimes, I myself forget events that occurred just a few days ago, yet I still remember moments from several years back. By understanding these reasons, they can be transformed into a memorization technique to make the learning process more effective and efficient. It turns out that the brain has a unique way of storing information, and it can even be said that our memories from childhood do not truly disappear; we simply need something to trigger their recall.